Biocontrol Potential of Siderophore Producing Heavy Metal Resistant Alcaligenes sp. and Pseudomonas aeruginosa RZS3 vis-à-vis Organophosphorus Fungicide - Sayyed, R. Z. (Springer-Verlag, 2011)
In present study in vitro phytopathogen suppression activity of siderophoregenic preparations of Ni and Mn resistant Alcaligenes sp. STC1 and Pseudomonas aeruginosa RZS3 SH-94B isolated from soil were found superior over the chemical pesticide. Siderophore rich culture broth and siderophore rich supernatant exerted antifungal activity against Aspergillus niger NCIM 1025, Aspergillus flavus NCIM 650, Fusarium oxysporum NCIM 1281, Alternaria alternata ARI 715, Cercospora arachichola, Metarhizium anisopliae NCIM 1311 and Pseudomonas solanacerum NCIM 5103. Siderophore rich broth and supernatant exhibited potent antifungal activity vis-à-vis oraganophosphorus chemical fungicide; kitazine. The minimum fungicidal concentration required was 25 μl for Aspergillus niger, Aspergillus flavus, Fusarium oxysporum, Cercospora arachichola, Metarhizium anisopliae, Pseudomonas solanacerum and 75 μl for A. alternata.